How Stalin and Roosevelt influenced the Federal Elections in 2017 East Germany - Mirja C. Hälbig; Jürgen R. Lorenz (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Exploiting differences in occupation status in East Germany in the last days of World War II and shortly thereafter, we find that regions which - due to their occupation status - experienced a drastic supply problem caused by the influx of great numbers of refugees fleeing from the Red Army in 1945 had a disproportionate increase in AfD votes from 2013 to 2017. We conclude that the "refugee crisis" in 2015, which dominated the campaign of the federal elections in 2017 and is considered as main determinant of voting for the AfD, activated the collective memory of this long-gone historic event and thereby shaped the current political landscape.
Keywords: D72; N44; Z13; 330